Environmental Ethics in the Perspective of Muhammad Qutb: A Philosophical Review and Its Relevance to the Modern Ecological Crisis - Abdul Rahman Munthe; Mardian Idris Harahap (Civiliza Publishing, 2026)
This research discusses the concept of environmental ethics from the perspective of Muhammad Qutb, emphasizing the relationship between humans, nature, and moral responsibility in Islamic teachings. The increasing environmental crisis, such as pollution, exploitation of natural resources, and ecosystem destruction, demonstrates the need for an ethical foundation capable of fostering human ecological awareness. This study aims to analyze Muhammad Qutb’s views on environmental ethics and their relevance to modern life. The research method employed is library research using a descriptive-analytical approach through the examination of Muhammad Qutb’s works and other supporting literature. The findings of the study indicate that, according to Muhammad Qutb, humans are khalifah (stewards) on earth who bear the responsibility of maintaining the balance of nature as part of Allah’s trust (amanah). In his view, environmental ethics are built upon the principles of tawhid (the oneness of God), balance (mīzān), responsibility, and the prohibition against causing destruction (fasād) on earth. This perspective affirms that the relationship between humans and the environment is not merely material, but also spiritual and moral. Muhammad Qutb’s concept of environmental ethics is relevant in addressing modern ecological challenges because it can encourage religious awareness and environmentally friendly behavior within society.